Appropriate operating room time allocations and half-day block time for low caseload proceduralists, including anesthesiologist pain medicine physicians in the State of Florida - Dexter, Franklin; Epstein, Richard H.; Podgorski, Edward M.; Pearson, Amy C.S. (Journal of clinical anesthesia, 2020)
We analyzed University of Iowa operating room data to estimate whether it would be economically rational to allocate, every two weeks, an operating room to anesthesiology pain medicine physicians or a half-day session to individual proceduralists. We investigated the generalizability of the results by studying anesthesiologist pain medicine physicians working at all hospitals and ambulatory surgery centers in the State of Florida. Observational, cohort study of spinal neuromodulation procedures. Hours of daily operating room time and cases by anesthesiologist pain medicine physicians at the University of Iowa, and in Florida in 2018. For each two-week period, we calculated the difference in hours between (1) the under-utilized time from allocating 8 h and (2) time-and-a-half times the over-utilized time from no allocated time. The mean greater cost from allocating 8 h vs 0 h equaled 3.89 h, significantly >0 (P = 0.0001, N = 77 periods). Sample mean activities were 0.79 cases and 1.64 h, <2.00 cases and 4.00 h, respectively (both P < 0.0001). Thus, no allocated time or block time should be planned. At least 76.6% (95% lower confidence limit) of Florida surgical facilities performing ≥1 neuromodulation procedures averaged <1.08 cases per two weeks. At least 89.6% of the facilities averaged <2 cases per two weeks. At least 88.8% of combinations of anesthesiologist and facility in Florida averaged fewer cases per two weeks than anesthesiologist proceduralists at the University of Iowa. At least 96.5% of the proceduralists averaged <2 cases per two weeks at each facility where they operated. Among anesthesiologist proceduralists in Florida using operating room time for neurostimulator procedures, most perform too few cases weekly for the economically appropriate planning of block time. Few Florida facilities would have enough cases, even potentially, to warrant allocating operating room time. •How should low caseload proceduralists schedule their operating room cases?•Studied anesthesiologist pain medicine physicians who should use open time•Results apply to the ≅98% such proceduralists in Florida with these low caseloads.